(untitled) ([Austin, Tex.], 2001)
A digital "textbook" that includes CD-ROM discs and a customized website to communicate the fundamentals of precalculus. Some of the features available for the student: a series of multimedia video lectures that are adaptable to any course syllabus, interactive exercises with feedback, review materials, real-life applications, a student help center and free technical support. Features for the professors: A custom website, custom reports and tracking, community features, test bank and test, free technical support and professor help center
Keywords: Algebra,Trigonometry,Functions; Computer-assisted instruction,Computer-assisted instruction,Computer-assisted instruction